New directions in metal phosphonate and fhosphinate chemistry - Shearan, Stephen J.I.; Stock, Norbert; Emmerling, Franziska; Demel, Jan; Wright, Paul A.; Demadis, Konstantinos D.; Vassaki, Maria; Costantino, Ferdinando; Vivani, Riccardo; Sallard, Sébastien; Salcedo, Inés R.; Cabeza-Díaz, Aurelio; et al. (MDPI www.mdpi.com/journal/crystals, 2019)
In September 2018, the First EuropeanWorkshop on Metal Phosphonates Chemistry brought together some prominent researchers in the field of metal phosphonates and phosphinates with the aim of discussing past and current research e orts and identifying future directions. The scope of this perspective article is to provide a critical overview of the topics discussed during the workshop, which are divided into two main areas: synthesis and characterisation, and applications. In terms of synthetic methods, there has been a push towards cleaner and more e cient approaches. This has led to the introduction of high-throughput synthesis and mechanochemical synthesis. The recent success of metal–organic frameworks has also promoted renewed interest in the synthesis of porous metal phosphonates and phosphinates. Regarding characterisation, the main advances are the development of electron di raction as a tool for crystal structure determination and the deployment of in situ characterisation techniques, which have allowed for a better understanding of reaction pathways. In terms of applications, metal phosphonates have been found to be suitable materials for several purposes: they have been employed as heterogeneous catalysts for the synthesis of fine chemicals, as solid sorbents for gas separation, notably CO2 capture, as materials for electrochemical devices, such as fuel cells and rechargeable batteries, and as matrices for drug delivery.
Keywords: Fósforo - Compuestos; Fosfatos; Pilas de combustible; Baterías de estado sólido; Conductividad eléctrica; X-ray and electron diffraction; Drug delivery; Rechargeable batteries; Proton conduction; Gas sorption/separation; Hterogeneous catalysis; In situ characterisation; Synthesis; Metal–organic frameworks; Layered materials; Metal phosphonates and phosphinate